Determinants And Outcomes Of Green Banking Adoption Of Pakistan’s Bank Branches: The Moderating Role Of Green Capability - Bukhari, Syed Asim Ali (2022)
The concept of Green Banking is a paradigm shift in the business ideology of a bank. Green Banking Adoption focuses on the reduction of the direct and indirect adverse environmental impacts arising from a bank’s business operation. A large number of developed and developing countries are adopting Green Banking. Pakistan is a developing country facing severe environmental degradation and resource degeneration. The environmentally hazardous business activities of various industries are one of the major sources of these challenges. Pakistan is in the initial stage of Green Banking Adoption. Meanwhile, the neighbouring developing countries of Pakistan like Bangladesh and India have made significant progress in terms of Green Banking Adoption. Therefore, the Pakistan banking industry urgently needs to control the alarming situation by minimizing its own adverse environmental impacts and increase the eco-friendly financing to industries. Based on the Institutional theory, the study examines the influence of stakeholders’ (top management, customer, competitor and community) pressure on Green Banking Adoption. It also examines the moderating effect of ‘green capability’ on the relationship between stakeholders’ pressures and Green Banking Adoption. The moderator is derived from pollution prevention capability of Natural Resource-Based View of the Firm. The research framework also examines the outcomes, i.e., (environmental, operational, intangible and economic) of Green Banking Adoption.